Do the Manual or Computer-Controlled Flowmeters Generate Similar Isoflurane Concentrations in Tafonius? - Raillard, Mathieu; Levionnois, Olivier; MacFarlane, Paul (Frontiers in Veterinary Science, 2019)
Introduction: Tafonius is an anaesthesia machine with computer-controlled monitor and ventilator. We compared the isoflurane fluctuations in the circuit with manual (MF) or computer-driven (CF) flowmeters, investigated the origin of the differences and assessed whether isoflurane concentration time course followed a one-compartment model. Material and Methods: A calibrated TEC-3 isoflurane vaporiser was used. Gas composition and flows were measured using a multiparametric monitor and a digital flowmeter. Measurements included: 1) Effects of various FiO2 with MF/CF on the isoflurane fraction changes in the breathing system during mechanical ventilation of a lung model; wash-in kinetic was fitted to a compartmental model; 2) Gas outflow at the common gas outlet (CGO) with MF/CF at different FiO2; 3) Isoflurane output of the vaporiser at various dial settings with MF/CF set at different flows without and with reduction of the CGO diameter. Results: 1) The 3% targeted isoflurane concentration was not reached; additional time was required to reach specific concentrations with CF (lowest FiO2, longer time). The exponential course fitted a two-compartment model; 2) Set and measured flows were identical with MF. With CF at 0.21 FiO2, flow was intermittently 7.6 L minute-1 or zero (mean total: 38% of the set flow); with CF at 1.00 FiO2, flow was 10.6 L minute-1 or zero (mean: 4-5.3 L minute-1); with 0.21<FiO2<1.00, combined flow was intermittent (maximum output: 15.6 L minute-1); 3) With MF, isoflurane output was matching dial setting at 5 L minute-1 but was lower at higher flows; with CF generating intermittent flows, isoflurane output was fluctuating. With the 4 mm diameter CGO, isoflurane concentration was close to dial setting with both MF and CF. With a 14 G CGO, isoflurane concentration was lower than dial setting with MF, higher with CF. Conclusions and clinical relevance: Using MF or CF led to different isoflurane fraction time course in Tafonius. Flows were lower than set with CF; the TEC-3 did not compensate for high/intermittent flows and pressures; the CGO diameter influenced isoflurane output.